Organizational Support for Green Hospital Initiatives: A Case Study - Rahman, Ferry Fadzlul; Haris, Fahni; Febriyanto, Kresna (Universitas Muhammadiyah Yogyakarta, 2024)
Organizational support plays a critical role in sustaining green hospital policies, particularly in managing medical waste, improving energy efficiency, and enhancing air quality. Implementing these practices is believed to enhance the quality of healthcare services, employee well-being, and the overall operational sustainability of hospitals. This study aimed to analyze factors influencing organizational support for green hospital initiatives, including employee engagement and motivation, participation and initiative, environmental training, green rewards, and employee satisfaction. Using an observational analytic design and a cross-sectional approach, we collected a research sample of 117 civil servants who met the inclusion and exclusion criteria from May to August 2024. Data were analyzed using Spearman's rank correlation and linear regression for multivariate analysis. The study demonstrated that involvement and motivation contributed 0.177, participation and initiative 0.116, and employee satisfaction 0.599 to organizational support for green hospital initiatives. The findings emphasize the importance of employee engagement, participation, satisfaction, and training in fostering sustainable healthcare practices. Strengthening organizational support enhances environmental practices, employee well-being, and operational efficiency. The study provides recommendations to improve the implementation of organizational support in hospitals.